METALS COALESCENCE IN COPPER CLIFF CONVERTER SLAG (Journal of Mining and Metallurgy, Section B: Metallurgy, 2016)
The aim of this investigation the effect of various additives on coalescence of various valuable metals from slags generated during Ni extraction. The analyzed fluxes were silica and lime while examined reductants were pig iron, ferrosilicon and copper-silicon compound. Slag was settled at the different holding temperatures for various times in conditions that simulated the industrial environment. The newly formed matte and slag were characterized by its chemical composition and morphology. Silica flux generated higher partition coefficients for copper and nickel than the addition of lime. Additives used as reducing agents had higher valuable metal recovery rates and corresponding partition coefficients than fluxes. Microstructural studies showed that slag formed after adding reductants consisted of primarily fayalite, with some minute traces of magnetite as secondary phase. Addition of 5 wt% of pig iron, ferrosilicon and copper-silicon alloys favored the formation of a metallized matte which increased Cu, Ni and Co recoveries. Addition of copper-silicon alloys with low silicon content was efficient in copper recovery but coalescence of the other metals was low. However, slag treatment with the Ferrosilicon facilitated the highest cobalt recovery while copper-silicon alloys with silicon content above 10wt% resulted in high coalescence of nickel and copper, 87 % and 72 % respectively.